The Novel Gene VpPR4-1 from Vitis pseudoreticulata Increases Powdery Mildew Resistance in Transgenic Vitis vinifera L. - Dai, Lingmin; Wang, Dan; Xie, Xiaoqing; Zhang, Chaohong; Wang, Xiping; Xu, Yan; Wang, Yuejin; Zhang, Jianxia (Frontiers in Plant Science, 2016)
Pathogenesis-related proteins (PRs) can lead to increased resistance of the whole plant to pathogen attack. Here, we isolate and characterize a PR-4 protein (VpPR4-1) from a wild Chinese grape Vitis pseudoreticulata which shows greatly elevated transcription following powdery mildew infection. Its expression profiles under a number of abiotic stresses were also investigated. Powdery mildew, salicylic acid, and jasmonic acid methyl ester significantly increased the VpPR4-1 induction while NaCl and heat treatments just slightly induced VpPR4-1 expression. Abscisic acid and cold treatment slightly affected the expression level of VpPR4-1. The VpPR4-1 gene was overexpressed in 30 regenerated V. vinifera cv. Red Globe via Agrobacterium tumefaciens-mediated transformation and verified by the Western blot. The 26 transgenic grapevines exhibited higher expression levels of PR-4 protein content than wild-type vines and six of them were inoculated with powdery mildew which showed that the growth of powdery mildew was repressed. The powdery mildew-resistance of Red Globe transformed with VpPR4-1 was enhanced inoculated with powdery mildew. Moreover, other powdery mildew resistant genes were associated with feedback regulation since VpPR4-1 is in abundance. This study demonstrates that PR-4 protein in grapes plays a vital role in defense against powdery mildew invasion.